2019
DOI: 10.18276/cej.2019.4-02
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship of the climbing level of sport climbers with selected anthropometric indicators and diet composition

Abstract: Climbing is becoming more and more popular. During 2020 Olympic Games this discipline will be competed for the first time. Individualized diet plays a significant role among representatives of all sport disciplines. The aim of this research was to evaluate the correlation between the level of advancement of sport climbers, selected anthropometric indicators and diet composition. The study involved 36 women and 65 men practicing sport climbing who completed the food record and the survey on the most difficult c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…As such, the elite male group had the lowest CHO intake (3.08 g/kg/BW). Monedero et al [ 13 ] (3.6 ± 1.0 g/kg/BW) and Gibson-Smith et al [ 12 ] (3.7 ± 0.9 g/kg/BW) found similar values, and a higher CHO intake was reported in our previous study [ 15 ] in the male (4.7 ± 1.4 g/kg/BW) and female (4.6 ±1.3 g/kg/BW) advanced groups. Sas-Nowosielski et al [ 11 ] reported a mean CHO intake of approximately 4 g/kg/BW and indicated that female participants were more likely to cut out CHOs.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…As such, the elite male group had the lowest CHO intake (3.08 g/kg/BW). Monedero et al [ 13 ] (3.6 ± 1.0 g/kg/BW) and Gibson-Smith et al [ 12 ] (3.7 ± 0.9 g/kg/BW) found similar values, and a higher CHO intake was reported in our previous study [ 15 ] in the male (4.7 ± 1.4 g/kg/BW) and female (4.6 ±1.3 g/kg/BW) advanced groups. Sas-Nowosielski et al [ 11 ] reported a mean CHO intake of approximately 4 g/kg/BW and indicated that female participants were more likely to cut out CHOs.…”
Section: Discussionsupporting
confidence: 87%
“…The anthropometric measurements of body mass and height for both sexes were similar to the participants of other studies involving sports climbers [ 11 , 12 , 15 , 16 ]. However, the body fat percentage was higher in the male groups [ 12 , 16 ].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation